2022
DOI: 10.1590/fst.36921
|View full text |Cite
|
Sign up to set email alerts
|

Quality of reduced sodium shrimp paste from shrimp head as alternative source

Abstract: The significantly decreased availability of the main raw materials for making shrimp paste is a big problem, while most by-products from shrimp processing, especially head, are not yet properly used. Therefore, using shrimp head for shrimp paste production is well motivated. However, traditional shrimp paste is high in salt and can impact health via hypertension, kidney, or cardiovascular disease. This study aimed to produce a reduced sodium shrimp head paste, using 12, 14 or 16-fold amount of shrimp heads rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
0
2
Order By: Relevance
“…DH of shrimp head in this experiment was around 1.81 ± 0.02% with similar values to DH 2.4% of shrimp head paste reported by Rujirapong et al (2022). This indicated that the freshness of shrimp head used in these two experiments was close to each other.…”
Section: Degree Of Hydrolysis (Dh)supporting
confidence: 88%
See 1 more Smart Citation
“…DH of shrimp head in this experiment was around 1.81 ± 0.02% with similar values to DH 2.4% of shrimp head paste reported by Rujirapong et al (2022). This indicated that the freshness of shrimp head used in these two experiments was close to each other.…”
Section: Degree Of Hydrolysis (Dh)supporting
confidence: 88%
“…Salt content in shrimp heads in this experiment was much higher (14.32 ± 0.55) than in the shrimp head in reported by Rujirapong et al (2022) with salt content at 4.96 ± 1.09 (dry basis) (Table 1). This was due to the remaining residue of chlorine solution during the washing step because silver nitrate was a main chemical used in the determination of chlorine and salt (The United States Environmental Protection Agency, 1994).…”
Section: Proximate Compositions and Salt Contentcontrasting
confidence: 46%
“…Chlorine determination also uses silver nitrate (United States Environmental Protection Agency, 1994) with reaction similar to the salt determination in this experiment. However, salt contents in shrimp pastes with garlic at 0%, 3%, and 5% after 90 days of fermentation were close to 28.05–42.48% (dry basis) of commercial Kapi (Kongpun & Kongrat, 2013) but lower than reported of Rujirapong et al (2020) which salt content was 24.26 ± 1.04%. The addition of garlic did not change protein, fat, ash, carbohydrate, or salt, as expected.…”
Section: Resultscontrasting
confidence: 41%